Low prevalence of mcr-1 in Escherichia coli from food-producing animals and food products in China - Cai-Yue Mei; Yue Jiang; Qin-Chun Ma; Meng-Jun Lu; Han Wu; Zhen-Yu Wang; Xinan Jiao; Jing Wang (BMC Veterinary Research, 2024)
Abstract Background mcr-1-positive Escherichia coli has emerged as a significant threat to human health, veterinary health, and food safety in recent years. After the prohibition of colistin as a feed additive in animal husbandry in China, a noticeable reduction in both colistin resistance and the prevalence of mcr-1 was observed in E. coli from animals and humans. Objectives To assess the prevalence of the colistin resistance gene mcr-1 and characterize its genetic context in E. coli strains derived from fecal and meat samples from food-producing animals in China. Methods A total of 1,353 fecal samples and 836 food samples were collected between 2019 and 2020 in China. E. coli isolates were identified using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and their susceptibility to colistin were determined using the broth microdilution method. The colistin-resistant E. coli isolates were screened for the presence of mcr by PCR analysis and sequencing. The minimal inhibitory concentrations (MICs) of 15 antimicrobial agents against the mcr-1-positive strains were further tested using the agar dilution method, conjugation assays were performed, and whole genome sequencing was performed using Illumina HiSeq. Results In total, 1,403 E. coli strains were isolated. Thirteen isolates from chicken meat (n = 7), chickens (n = 3), and pigs (n = 3) were resistant to colistin with MIC values of 4 to 16 mg/L, and carried mcr-1. All mcr-1-positive strains, except for isolate AH20PE105, contained multiple resistance genes and exhibited multidrug-resistant phenotypes. They belonged to 10 sequence types (STs), including a novel ST (ST14521). mcr-1 was located on IncI2 (n = 9), IncX4 (n = 2), and IncHI2 (n = 2) plasmids, which were highly similar to other mcr-1-carrying plasmids sharing the same incompatibility type. Seven mcr-1-carrying plasmids could be successfully conjugally transferred to E. coli C600. Conclusions While the low prevalence of mcr-1 (0.93%) identified in this study may not immediately seem alarming, the very emergence of this gene merits attention given its implications for colistin resistance and public health. Hence, ongoing surveillance of mcr-1 in E. coli remains crucial.